2012
DOI: 10.1213/ane.0b013e31823a088c
|View full text |Cite
|
Sign up to set email alerts
|

Procoagulant Activity in Hemostasis and Thrombosis

Abstract: Virchow’s triad is traditionally invoked to explain pathophysiologic mechanisms leading to thrombosis, alleging concerted roles for abnormalities in blood composition, vessel wall components, and blood flow in the development of arterial and venous thrombosis. Given the tissue-specific bleeding observed in hemophilia patients, it may be instructive to consider the principles of Virchow’s triad when investigating mechanisms operant in hemostatic disorders as well. Blood composition (the function of circulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
172
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(181 citation statements)
references
References 137 publications
6
172
0
3
Order By: Relevance
“…31 Virchow's triad traditionally explains a pathophysiologic mechanism of thrombus formation, and the triad includes abnormalities in blood composition, vessel wall components and blood flow. 35 In the present study, the occurrence of SEC was independently associated with LAVI, LAAV and RHI, suggesting that endothelial dysfunction was an important determinant of SEC in addition to LA remodeling and low LAA flow.…”
Section: Measurement Of Peripheral Endothelial Functionsupporting
confidence: 55%
“…31 Virchow's triad traditionally explains a pathophysiologic mechanism of thrombus formation, and the triad includes abnormalities in blood composition, vessel wall components and blood flow. 35 In the present study, the occurrence of SEC was independently associated with LAVI, LAAV and RHI, suggesting that endothelial dysfunction was an important determinant of SEC in addition to LA remodeling and low LAA flow.…”
Section: Measurement Of Peripheral Endothelial Functionsupporting
confidence: 55%
“…The first factor is represented by hypercoagulability, which is very common in myeloproliferative diseases such as leukemia, lymphoma, essential thrombocythemia, and polycythemia vera. 29 The second factor is represented by the mechanical injury of the arterial wall, which can occur in artery catheterization or due to circulating leukocytes and platelets in blood stream. [29][30][31] In 2008, Ruggeri et al presented the results of a large study that found an increased risk of excessive bleeding (7.3%) and vascular occlusion (7.7%) in patients with multiple personality disorder and thrombocytosis.…”
Section: Risk Of Artery Catheterization In Patients With Essential Thmentioning
confidence: 99%
“…29 The second factor is represented by the mechanical injury of the arterial wall, which can occur in artery catheterization or due to circulating leukocytes and platelets in blood stream. [29][30][31] In 2008, Ruggeri et al presented the results of a large study that found an increased risk of excessive bleeding (7.3%) and vascular occlusion (7.7%) in patients with multiple personality disorder and thrombocytosis. 32 Vidwan et al reported the results of a retrospective study on 3,466 patients undergoing coronary angiography, in which they found significant correlations between the risk of bleeding, vascular complications, and elevated platelet counts.…”
Section: Risk Of Artery Catheterization In Patients With Essential Thmentioning
confidence: 99%
“…Further research is required validating the risk factors for VTE in robotic surgeries. Venous stasis (part of the Virchow`s triad [21]) is one of the most important factors in the development of thromboembolism. Theoretically, prolonged pneumoperitoneum can increase the intra-abdominal pressures and compress the vessels.…”
Section: Background Risk Factors For Venous Thromboembolism and Methomentioning
confidence: 99%